2009
DOI: 10.1021/pr900461c
|View full text |Cite
|
Sign up to set email alerts
|

Anxa2 Plays a Critical Role in Enhanced Invasiveness of the Multidrug Resistant Human Breast Cancer Cells

Abstract: Multidrug resistance (MDR) is the major cause of failure in cancer chemotherapy. Recent reports even suggest that MDR is associated with elevated invasion and metastasis of tumor cells. In the current study, we used a proteomic approach to identify genes that play an important role in MDR induced cell migration. 2D-PAGE and MALDI-TOF/MS-based proteomics approach were used to separate and identify differentially expressed proteins between MCF-7 and MCF-7/ADR, a p-glycoprotein-overexpressing adriamycin-resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 41 publications
4
75
0
Order By: Relevance
“…The establishment of SGC7901/DDP cells has provided a powerful tool for further study of the effect and mechanism of ANXA2 on MDR. The recent report showed that the expression of ANXA2 was increaed in resistant MCF-7/ADR cells, but not in MCF-7 cells [28]. In the present study, we found that the expression of ANXA2 was significantly higher in SGC7901/ DDP cells than in SGC7901 cells, indicating that ANXA2 played a key role in the development of MDR of gastric cancer.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The establishment of SGC7901/DDP cells has provided a powerful tool for further study of the effect and mechanism of ANXA2 on MDR. The recent report showed that the expression of ANXA2 was increaed in resistant MCF-7/ADR cells, but not in MCF-7 cells [28]. In the present study, we found that the expression of ANXA2 was significantly higher in SGC7901/ DDP cells than in SGC7901 cells, indicating that ANXA2 played a key role in the development of MDR of gastric cancer.…”
Section: Discussionsupporting
confidence: 44%
“…Previous data suggest that ANXA2 may take part in mechanism of MDR in bladder and breast cancer [28,29]. To explore the effect and mechanism of ANXA2 on MDR in GC, we successfully established a DDP resistant cell line SGC7901/DDP after continual exposure of SGC7901 to cisplatin, a major chemotherapy drug in gastric carcinoma treatment [30].The results showed that the resistance index was 23.4.…”
Section: Discussionmentioning
confidence: 99%
“…39). RNAimediated silencing of AnxA2 impairs the migration of human epithelial colorectal adenocarcinoma cells (40) and glioma cells (41) and reduces the invasiveness of breast cancer cells (18), all highlighting the potential importance of AnxA2 in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…To silence AnxA2 expression, oligonucleotides 5Ј-GATCCCCGGTCTGAATTCAAGAGAAAGTTTCAAGA-GAACTTTCTCTTGAATTCAGACCTTTTTA-3Ј (forward) and its complement 5Ј-AGCTTAAAAAGGTCTGAATTCA-AGAGAAAGTTCTCTTGAAACTTTCTCTTGAATTCAG-ACCGGG-3Ј (reverse) were used (AnxA2 targeting sequences described previously in Ref. 18 are underlined). Inserts were cloned in pSuper.retro.puro vector (OligoEngine, Seattle, WA).…”
Section: Methodsmentioning
confidence: 99%
“…annexin ii (anXa2) is a member of a family of calcium-dependent phospholipid membrane-binding proteins that contains a conserved repeating domain of approximately 70 amino acids. anXa2 has been shown to concentrate in lipid rafts and likely participates in ion channel regulation and the formation of tight junctions (4,5). it is up-regulated in response to physiologic stress, and inhibits cellular mobility when levels are restored in prostate cancer cells in culture.…”
Section: Introductionmentioning
confidence: 99%